USEFUL TIPS FOR TEACHING VOCABULARY IN EFL CLASSES - Saydivaliyeva, Barno (Журнал иностранных языков и лингвистики, 2023)
Our article looks at the useful effects and benefits of vocabulary for students learning English as a second language.